2018
DOI: 10.1039/c7ta09535j
|View full text |Cite
|
Sign up to set email alerts
|

Sensing mechanism of ethanol and acetone at room temperature by SnO2 nano-columns synthesized by aerosol routes: theoretical calculations compared to experimental results

Abstract: A useful feedback loop: insights from theoretical calculations are used for rational design of nanosensors and for elucidating surface interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 79 publications
5
71
0
Order By: Relevance
“…A typical XRD pattern of a printed SnO 2 layer with the as‐prepared ink is shown in Figure a, with dominant peaks at 26.49°, 33.75°, and 51.74° corresponding to (110), (101), and (211), indicating the tetragonal rutile phase of SnO 2 nanoparticles. Notably, it has been reported that the adsorption of ethanol and acetone on surface facets of (110) and (101) is thermodynamically favorable, and thus the as‐printed SnO 2 thin films is suitable for gas detection . As shown in the SEM and EDS images (Figure b,c; Figure S9, Supporting Information), the inkjet printed SnO 2 layer is uniform and continuously bridges the Ag integrated electrodes with an electrode width of 50 µm and interspace of 100 µm.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…A typical XRD pattern of a printed SnO 2 layer with the as‐prepared ink is shown in Figure a, with dominant peaks at 26.49°, 33.75°, and 51.74° corresponding to (110), (101), and (211), indicating the tetragonal rutile phase of SnO 2 nanoparticles. Notably, it has been reported that the adsorption of ethanol and acetone on surface facets of (110) and (101) is thermodynamically favorable, and thus the as‐printed SnO 2 thin films is suitable for gas detection . As shown in the SEM and EDS images (Figure b,c; Figure S9, Supporting Information), the inkjet printed SnO 2 layer is uniform and continuously bridges the Ag integrated electrodes with an electrode width of 50 µm and interspace of 100 µm.…”
mentioning
confidence: 93%
“…SnO 2 as a n‐type semiconductor, is one of the most commonly used material for gas sensing mainly due to its low cost, stability, and repeatability . While metal oxide sensors normally require high operation temperature (over 200 °C) to achieve high sensitivity and fast recovery, recent studies demonstrated the SnO 2 has the capability for volatile organic compounds detection under room temperature, which eliminate the integration of heaters and thermal isolation units . Especially for portable and wearable electronics, room temperature operational sensors are highly desirable for device miniaturization and long cruising time without extra power consumption for heaters .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Semiconducting metal oxide-based gas sensors have aroused signicant research interest owing to their low cost, easy production and high sensitivity, stability, and scalability. [1][2][3][4][5] They are broadly applied in elds ranging from health monitoring and medical detection to safety. 3,[6][7][8] Among the currently available metal oxide semiconductors, SnO 2 , as a typical n-type semiconductor with a 3.6 eV band gap, has been extensively studied in the eld of gas sensors and applied to the detection of a number of different gases such as HCHO, CH 3 OH, NH 3 , C 2 H 6 O, CO, SO 2 , CH 4 and H 2 S. 6,[9][10][11][12][13][14] However, the practical applications of SnO 2 have been limited due to its low selectivity, high operating temperature and unsatisfactory sensing response.…”
Section: Introductionmentioning
confidence: 99%